The Effect of Variations of Red Bricks, Sand, Sawdust, and Green Tea (Camellia sinensis) Media on the Fat Content of Salted Egg Yolks - Nur Hidayati; Mardiyono Mardiyono; Dian Kresnadipayana (Fakultas Ilmu Kesehatan Universitas Setia Budi Surakarta, 2022)
Salting is done to extend the shelf life of duck eggs. A variety of media can be used for salting eggs, including a mixture of salt, sand, red brick, sawdust, and brewed tea. Salted eggs are popular among the general public, but they contain a lot of fat, which, if consumed in excess, can cause blood vessel blockage (atherosclerosis). Green tea is a plant that has many benefits, one of which is that it can help people lose weight. Duck eggs were ripened for 12 days in a variety of salting media with different ingredients for this study. Red bricks, sand, sawdust, salt, and brewed green tea are among the materials used. This study aimed to determine the fat content of salted egg yolks using the Soxhlet extraction method, as well as the color, aroma (smell), and taste of salted eggs. The data in this study were analyzed using One-Way ANOVA and the results revealed that variations in salting media had a significant effect on fat content in salted egg yolks. The results showed the changes in fat content in salted egg yolks without treatment with a fat content of 36.28 percent, and with treatment with media A (sand, red bricks, and sawdust); media B (sand, red bricks, and sawdust); media 1 (media A added with green tea); and media 2 (media B added with green tea), with the fat contents of 35.22%; 32.86%, and 30.49%. Mixed media of green tea affects the fat content of salted egg yolks, from 36.50% to 32.86% and 30.49%.